Telotristat ethyl in carcinoid syndrome: safety and efficacy in the TELECAST phase 3 trial - Pavel, Marianne Ellen; Gross, David J.; Benavent, Marta; Perros, Petros; Srirajaskanthan, Raj; Warner, Richard R. P.; Kulke, Matthew H.; Anthony, Lowell B.; Kunz, Pamela L.; Hoersch, Dieter; Weickert, Martin O.; Lapuerta, Pablo; et al. (Endocrine-Related Cancer, 2018)
Telotristat ethyl, a tryptophan hydroxylase inhibitor, was efficacious and well tolerated in the phase 3 TELESTAR study in patients with carcinoid syndrome (CS) experiencing ≥4 bowel movements per day (BMs/day) while on somatostatin analogs (SSAs). TELECAST, a phase 3 companion study, assessed the safety and efficacy of telotristat ethyl in patients with CS (diarrhea, flushing, abdominal pain, nausea or elevated urinary 5-hydroxyindoleacetic acid (u5-HIAA)) with <4 BMs/day on SSAs (or ≥1 symptom or ≥4 BMs/day if not on SSAs) during a 12-week double-blind treatment period followed by a 36-week open-label extension (OLE). The primary safety and efficacy endpoints were incidence of treatment-emergent adverse events (TEAEs) and percent change from baseline in 24-h u5-HIAA at week 12. Patients (N = 76) were randomly assigned (1:1:1) to receive placebo or telotristat ethyl 250 mg or 500 mg 3 times per day (tid); 67 continued receiving telotristat ethyl 500 mg tid during the OLE. Through week 12, TEAEs were generally mild to moderate in severity; 5 (placebo), 1 (telotristat ethyl 250 mg) and 3 (telotristat ethyl 500 mg) patients experienced serious events, and the rate of TEAEs in the OLE was comparable. At week 12, significant reductions in u5-HIAA from baseline were observed, with Hodges-Lehmann estimators of median treatment differences from placebo of -54.0% (95% confidence limits, -85.0%, -25.1%, P < 0.001) and -89.7% (95% confidence limits, -113.1%, -63.9%, P < 0.001) for telotristat ethyl 250 mg and 500 mg. These results support the safety and efficacy of telotristat ethyl when added to SSAs in patients with CS diarrhea (ClinicalTrials.gov identifier: Nbib2063659).
EVALuna2:34110